Transformation, Internalization, and Media Socialization of Core Values for State Civil Apparatus (ASN) - Syaputra, Hendry; Abdullah, Aceng; Sjafirah, Nuryah Asri (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
In 2021, the Ministry of PANRB launched the Core Values and Employer Branding for the State Civil Apparatus (ASN) in Indonesia, known as "BerAKHLAK." This study aims to provide an overview of the transformation, internalization, and socialization of the BerAKHLAK core values within Statistics Indonesia (BPS) as an organizational culture. Additionally, the research will explore the challenges of transforming BPS's existing core values into BerAKHLAK. The study employs a qualitative approach with a triangulation method, utilizing interviews, data archives, and observations. The findings reveal that the transformation, socialization, and internalization process is not an easy task, resulting in the formation of a network of change agents within BPS. These change agents play a crucial role as catalysts, drivers of change, problem solvers, and mediators. Dissemination and internalization of the BerAKHLAK core values among ASN at BPS are conducted through various media channels, including social media platforms such as Instagram, WhatsApp, and YouTube. Additionally, physical mediums like banners, billboards, and logo placements on uniforms, hats, folders, and even PowerPoint drafts used for presentations are utilized. Capacity building activities such as training, benchmarking, workshops, seminars, and focus group discussions are recommended to further enhance development. This study suggests further research on the transformation, internalization, and socialization of the BerAKHLAK core values as an organizational culture in other government institutions.